2015
DOI: 10.1007/s13277-015-3233-5
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and anergy of T cell induced by pancreatic stellate cells-derived galectin-1 in pancreatic cancer

Abstract: Galectin-1, a β-galactoside-binding protein implicated in cancer cell immune privilege, was highly expressed in activated pancreatic stellate cells (PSCs). This study was designed to investigate the relationship between PSC-derived galectin-1 and tumor immunity in pancreatic cancer. Isolated PSCs were identified as normal pancreas cells (hNPSCs) or pancreatic cancer cells (hCaPSCs) by immunohistochemical staining for α-SMA and vimentin, and galectin-1 expression was evaluated by Western blotting and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 51 publications
1
70
0
Order By: Relevance
“…Caspase-3 is the effector molecule in the apoptotic cascade signaling pathway and is the executive protein of apoptosis (22). As a DNA damage repair molecule, PARP is degraded by caspase-3 and other cysteine proteinases during apoptosis, and its degradation is regarded as an early molecular sign of apoptosis (23). In the present study, it was also identified that down-expression of PARP-1 (via olaparib) significantly decreased the cellular viability of PanC-1 cells, increased p53 protein expression, decreased expression of pro-caspase-3, increased caspase-3 activity and suppressed Bcl-2 protein expression following the inhibition of ATM activity.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 is the effector molecule in the apoptotic cascade signaling pathway and is the executive protein of apoptosis (22). As a DNA damage repair molecule, PARP is degraded by caspase-3 and other cysteine proteinases during apoptosis, and its degradation is regarded as an early molecular sign of apoptosis (23). In the present study, it was also identified that down-expression of PARP-1 (via olaparib) significantly decreased the cellular viability of PanC-1 cells, increased p53 protein expression, decreased expression of pro-caspase-3, increased caspase-3 activity and suppressed Bcl-2 protein expression following the inhibition of ATM activity.…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine ligand/receptor has been demonstrated to be a strong chemoattractant for lymphocytes [34]. PSCs also induce T cell apoptosis and anergy by expressing galectin-1 [35]. PSCs may crosstalk with TAMs in PanIN, and these cell populations activate each other by secreting various soluble factors.…”
Section: Pdac Stromamentioning
confidence: 99%
“…In addition to the plethora of cytokines and chemokines that are common to aPSCs and Kras-mutant tumor cells, aPSCs secrete a number of unique factors that independently contribute to the immune contexture of PDAC. For example, galectin 1 was found to be a principal mediator of T-cell suppression in PanINs and PDAC and is uniquely expressed by aPSCs (Tang et al 2012(Tang et al , 2015. Zambirinis and colleagues (2015) showed that CCL3 secretion by aPSCs was required for the recruitment of Treg cells in KPC mice.…”
Section: Stellate Cellsmentioning
confidence: 99%